Review of Prognostic Expression Markers for Clear Cell Renal Cell Carcinoma - Petitprez, Florent; Ayadi, Mira; de Reyniès, Aurélien; Fridman, Wolf H.; Sautès-Fridman, Catherine; Job, Sylvie (Frontiers in Oncology, 2021)
Context: The number of prognostic markers for clear cell renal cell carcinoma (ccRCC) has been increasing regularly over the last 15 years, without being integrated and compared. Objective: Our goal was to perform a review of prognostic markers for ccRCC to lay the ground for their use in clinics. Evidence acquisition: Pubmed database was searched to identify RNA and protein markers whose expression level was reported as associated with survival of ccRCC patients. Relevant studies were selected through cross-reading by two readers. Evidence synthesis: We selected 249 studies reporting an association to prognostic of either single markers or multiple-marker models. Altogether, these studies were based on a total of 341 distinct markers and 13 multiple-marker models. Twenty percent of these markers were involved in four biological pathways altered in ccRCC: cell cycle, angiogenesis, hypoxia and immune response. The main genes (VHL, PBRM1, BAP1 and SETD2) involved in ccRCC carcinogenesis are not the most relevant for assessing survival. Conclusion: Among single markers, the most validated markers were KI67, BIRC5, TP53, CXCR4 and CA9. Of the multiple-marker models, the most famous model, ClearCode34, has been highly validated on several independent datasets but its clinical utility has not yet been investigated. Patient summary: Over the years, the prognosis studies have evolved from single markers to multiple-marker models. Our review highlights the highly validated prognostic markers and multiple-markers models and discusses their clinical utility for a better therapeutic care.